Sikap Hamba Tuhan terhadap Jemaat yang Mudur dari Pelayanan - Kejar Hidup Laia (Sekolah Tinggi Teologi Baptis Medan, 2020)
Becoming God's Servant is a special call from God. God's Servant is the call of the congregation to someone who is considered to have godliness in his faith and actions of daily life. Whereas the word